Damages to biological macromolecules in gonadal subcellular fractions of scallop Chlamys farreri following benzo[a]pyrene exposure: Contribution to inhibiting gonadal development and reducing fertility. (15th August 2021) - Yang, Yingying; Pan, Luqing; Zhou, Yueyao; Xu, Ruiyi; Miao, Jingjing; Gao, Zhongyuan; Li, Dongyu
Abstract: Benzo[a]pyrene (B[a]P), a representative polycyclic aromatic hydrocarbon (PAH) compound in marine ecosystem, has great potential for chronic toxicity to marine animals. It is becoming increasingly apparent that reproductive system is the major target of B[a]P, but the adverse effects of B[a]P on subcellular fractions in bivalve gonads have not been elucidated. Scallops Chlamys farreri are used as the experimental species since they are sensitive to environmental pollutants. This study was conducted to investigate how B[a]P affected the gonadal subcellular fractions, including plasma membrane, nucleus, mitochondria and microsome in scallops, and whether subcellular damages were related to reproductive toxicity. The results showed that mature gametes' counts were significantly decreased in B[a]P-treated scallops. Three biological macromolecules (viz., DNA, lipids and proteins) in gonadal subcellular fractions obtained by differential centrifugation suffered damages, including DNA damage, lipid peroxidation and protein carbonylation in B[a]P treatment groups. Interestingly, mitochondria and microsome were more vulnerable to lipid peroxidation and protein carbonylation than plasma membrane and nucleus, meanwhile males were more susceptible to DNA damage than females under B[a]P exposure. In addition, histological analysis showed that B[a]P delayed gonadal development in C. farreri . To summarize, our results indicated that B[a]P caused damages to biological macromolecules in gonadal subcellular fractions and then induced damages to gonadal tissues of C. farreri, which further inhibited gonadal development and ultimately leaded to reduction in fertility. This study firstly reports the impacts of PAHs on subcellular fractions in bivalves and their relationship with reproductive toxicity. Moreover, exposure of reproductive scallops to B[a]P leads to defects in reproduction, raising concerns on the possible long-term consequences of PAHs for natural populations of bivalves. Graphical abstract: Image 1 Highlights: B[a]P reduced fertility in mature scallops. Gonadal mitochondria and microsome were more vulnerable to lipid peroxidation and protein carbonylation induced by B[a]P. Testis was more susceptible to DNA damage than ovary under B[a]P exposure. B[a]P inhibited gonadal development. Abstract : Mitochondria and microsome were more vulnerable to lipid peroxidation and protein carbonylation. And testis were more susceptible to DNA damage than ovary.